Training Need Assessment and Impact of Training on Women Dairy Farmers - Saroj Kumari , Nishi Sethi , J. S. Malik Vinay Mehala and Vikram Yogi, (Indian Journal of Extension Education, 2017)
The present study was conducted in Hisar district of Haryana state. From Hisar district, two blocks Adampur and Hisar-Iwere selected randomly. From selected blocks, two villages, namely Siswal from Adampur and Dabra from Hisar-1 wereselected by random technique. From each selected village, 50 women were selected randomly, thus making a total sampleof 100 women. From selected villages, 20 women who were interested in training in dairy farming were selectedpurposively. Majority of the respondents were of middle age, illiterate, married and belonged to joint family. Eighty-fourper cent respondents had no social participation and had small herd size. Most of the respondents (25%) had medium landholding and lived in pucca houses. Training need score was obtained highest for the task housing management of cattleshed (mean 76.83 and rank-I), followed by animal health, watering, wallowing and bathing, breeding, post-parturitioncare, bedding, care and management of calves, feeding, marketing, farm management and accounting and milking andmilk product preparation ranked from II to XI, respectively. Similarly, training need was high for animal health (rankedII) but dairy farm women had high knowledge (74.1) and low difficulty (2.19). It was surprise to see that after computingfrequency, importance, difficulty and knowledge of last ranks were given to farm management and accounting (X rank)and milking and milk product preparation (XI rank) but highest learning difficulty by dairy farm women was perceived forthese components. It was also interesting to note that negligible percentage of respondents performed tasks of dairy farmmanagement, accounting and marketing where money matters were involved.